Lembar Aktivitas Mahasiswa Materi Integral Jumlah Riemann Berdasarkan Teori Aksi, Proses, Objek, Skema (APOS) - Maya Saftari; Sariman (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
This study produced a prototype of Riemann's number of teaching materials based on APOS theory. The student activity sheet (LAM) based on APOS theory was designed to help students understand the integral of the subject matter of Riemann quantities. The teaching materials design process was divided into two stages, namely preliminary study and formative evaluation. In the preliminary study stage, the researchers prepared and designed teaching materials in the form of student activity sheets for the subject of Riemann's Amount based on the APOS theory (Action, Process, Object, and Scheme). In the formative evaluation stage, researchers evaluated and revised the results of the design of teaching materials. The evaluation results in the form of comments and suggestions were used to revise the products produced, namely the first, second, and third prototypes. From these three stages, the first prototype that the researcher designed was revised based on the comments from the validator, namely expert review and several students. The second prototype was revised based on comments from several groups of students in small groups. The third prototype was the final design result used for field testing at the field test stage. The trials conducted showed that the goal of producing a product design that had a potential effect (usability) in the mathematics learning process had been achieved.